Enjoying what comes naturally: the Church of England and sexuality in the 1930s - Chapman, MD (Cambridge University Press, 2024)
This article begins by outlining the changing approach in Anglican attitudes to contraception at the Lambeth Conference of 1930, where birth control was permitted for married couples and sex separated from the possibility of procreation. The logical extension of this teaching, as was noted by Bishop Charles Gore, was that other forms of sexual pleasure, including homosexuality, which was increasingly seen as a 'natural' condition, might eventually be sanctioned by the church. Later in the 1930s, a series of letters by Robert Reid to Cosmo Gordon Lang, archbishop of Canterbury, shows the beginnings of a campaign for a change of policy. At the outbreak of the Second World War, the Anglican writer Kenneth Ingram published Sex-Morality Tomorrow, which pressed for full homosexual equality and provoked calls to William Temple to suppress the book. 1940 proved an inopportune moment for reform of church teaching on homosexuality, which continues to elicit widespread controversy.